Dynamic Monitoring of CFRP Strengthened Bridges: A Distributed Sensing Approach Under Bridge–Vehicle Coupling - Bitao Wu; Sicheng Fu; Yan Gong; Yanchao Shao; Zhenwei Zhou; Haitao Wang (Buildings)
To achieve a rapid assessment of reinforced bridges without interrupting traffic, the method and influence parameters for evaluating prestressed CFRP (Carbon Fiber Reinforced Polymer) plate-strengthened bridges were investigated based on distributed sensing while considering the bridge–vehicle coupling. Firstly, based on the principle of distributed monitoring, the strain influence line equation for prestressed CFRP plate-strengthened bridges under moving vehicle loads was derived. An evaluation index and method for assessing strengthening effectiveness based on distributed strain monitoring was proposed. Numerical simulation experiments were conducted for verification, in which a simulation method for solving the bridge–vehicle coupling vibration response based on the displacement contact method was studied. Relevant example verifications were carried out to prove the correctness of this method. On this basis, a dynamic performance analysis of the bridge before and after strengthening under bridge–vehicle coupling was performed. Finally, a study on influencing parameters was conducted to investigate the impact of different prestress levels of CFRP plates, different vehicle speeds, and different vehicle axle loads on the evaluation method. The results demonstrate that the bridge–vehicle coupling calculation model based on the displacement contact method can effectively simulate the dynamic response of the bridge after reinforcement. The evaluation method based on distributed sensing monitoring is unaffected by the speed and axle load of the vehicle, enabling the assessment of the condition and stress state of the strengthened bridge.